NOD mice are functionally deficient in the capacity of cross‐presentation. Issue 6 (20th January 2015) - Lee, Chin‐Nien; Lew, Andrew M; Shortman, Ken; Wu, Li
Abstract : Cross‐presentation by CD8 + conventional dendritic cells (cDCs) is involved in the maintenance of peripheral tolerance and this process is termed cross‐tolerance. Previous reports showed that non‐obese diabetic (NOD) mice have reduced number of splenic CD8 + cDCs compared with non‐diabetic strains, and that the administration of Flt3L to enhance DC development resulted in reduced diabetes incidence. As CD8 + cDCs are the most efficient antigen cross‐presenting cells, it was assumed that reduced cross‐presentation by non‐activated, tolerogenic CD8 + cDC predisposes to autoimmune diabetogenesis. Here we show for the first time that indeed NOD mice have a defect in autoantigen cross‐presentation capacity. First, we showed that NOD CD8 + cDCs were less sensitive to iatrogenic cytochrome c, which had previously been shown to selectively deplete CD8 + cDCs that functionally cross‐present. Second, we found that proliferation of islet‐specific glucose‐6‐phosphatase catalytic subunit‐related protein (IGRP)‐specific CD8 + T cells was impaired in NOD compared with non‐obese diabetes resistant mice after immunization with cell associated recombinant fusion protein containing the cognate IGRP peptide. This study, therefore, suggests that the reduced number of CD8 + cDCs in NOD mice, coupled with the reduced capacity to cross‐present self‐antigens, reduces the overall capacity to maintain peripheral tolerance in the spontaneous autoimmune type 1 diabetes mice.